2017
DOI: 10.1080/24750573.2017.1342751
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pharmacologic therapies accompanied by behavioural therapy on smoking cessation success: a prospective cohort study in Turkey

Abstract: OBJECTIVE: The main objective of this study is to compare the rate of smoking cessation in the first month, third month, sixth month, first-year, and second year among those who quit smoking following different pharmacological and behavioural therapies administered at the Selcuk University's Smoking Cessation Clinic in Turkey. METHODS: In this study, 3322 people who presented to the clinic in order to quit smoking were advised one of the most suitable medical treatments (varenicline, bupropion, NRT) accompanie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Similarly, it is stated in the study by Marakoğlu et. al that smoking cessation period in the group using varenicline was longer than bupropion and NRT (28).…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, it is stated in the study by Marakoğlu et. al that smoking cessation period in the group using varenicline was longer than bupropion and NRT (28).…”
Section: Discussionmentioning
confidence: 95%
“…The outcomes and aims of the included studies are summarized in Table 3. The most commonly reported outcome was the quit rate (n=18) 36,37,40,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] , followed by cessation rate (n=8) 39,41,[56][57][58][59][60][61] , sustained abstinence (n=1) 35 , fail to quit (n=1) 62 , cessation survival rate (n=1) 38 , and success rate (n=1) 35 . The majority of studies utilized a self-reported questionnaire to estimate quit rates, while some others used the carbon monoxide breath test to determine quitting state (n=19) 35-37,39-41,43,44,46-48,50-53, 55-57,59 .…”
Section: Outcomes Of the Tc Programsmentioning
confidence: 99%
“…A number of individual factors are associated with the effectiveness of TC programs. For example, factors found to be associated with reduced effectiveness include individual withdrawal symptoms 39,45,47,57,63 , high nicotine dependence rate 36,38,43,49,52,60,62,63 , poor knowledge on how to quit 45 , change in attitudes and behaviors 43,56 , stress 47,48 , number of cigarettes smoked per day 62,63 , inability to afford higher priced medications 49,50,62 , and concern about gaining weight 51,63 . Other individual factors that were found to be associated with effective TC programs included older age 51,62 , female gender 61 , knowledge on the benefits of tobacco cessation 35,59 , health issues 41,47,53,54,59,[61][62][63] , higher education level 48,54 , religious beliefs 59 , and adherence to treatment 51 .…”
Section: Individual Factorsmentioning
confidence: 99%
“…Passive exposure to cigarette smoke contributes to the development of cardiac diseases, cancer and other diseases, causing about 1.2 million additional deaths per year (1). In the literature, it is thought that there will be 8 million deaths worldwide due to smoking in 2030 (2). Tobacco causes addiction with nicotine and may cause cardiovascular diseases, stroke, chronic lung disease, lung cancer and other types of cancer (3,4).…”
Section: Sigara Bağımlılığında Aile Terapisi: Olgu Sunumu öZetmentioning
confidence: 99%